2021
DOI: 10.1055/s-0041-1722874
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Cohort Study on Mortality and Neurodevelopmental Outcomes of Preterm Very Low Birth Weight Infants Born to Mothers with Hypertensive Disorders of Pregnancy

Abstract: Objective We examined the effects of maternal hypertensive disorders of pregnancy (HDP) on the mortality and neurodevelopmental outcomes in preterm very low birth weight (VLBW) infants (BW ≤1,500 g) based on their intrauterine growth status and gestational age (GA). Study Design We included singleton VLBW infants born at <32 weeks' gestation registered in the Neonatal Research Network Japan database. The composite outcomes including death, cerebral palsy (CP), and developmental delay (DD) at 3 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…Another study found that the factors such as sex, gestational age, birth weight, multiple births, and antenatal steroids could affect the mortality of EP infants ( 16 ). In our study, after matching these factors, there was no significant difference in survival rate between the two groups, which was consistent with the results of Kono et al ( 7 , 8 ), but inconsistent with the results reported in Japan ( 13 ).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Another study found that the factors such as sex, gestational age, birth weight, multiple births, and antenatal steroids could affect the mortality of EP infants ( 16 ). In our study, after matching these factors, there was no significant difference in survival rate between the two groups, which was consistent with the results of Kono et al ( 7 , 8 ), but inconsistent with the results reported in Japan ( 13 ).…”
Section: Discussionsupporting
confidence: 61%
“…Over the past years, several studies have reported the effect of HDP on the clinical outcomes of preterm infants, but these conclusions are contradictory, especially in mortality (4)(5)(6)(7)(8), bronchopulmonary dysplasia (BPD) (4,5,(9)(10)(11)(12), and intraventricular hemorrhage (IVH) (4,5,10,(13)(14)(15). The inconsistency of these results may be related to different study populations and inconsistent baseline characteristics of the subjects.…”
Section: Introductionmentioning
confidence: 99%
“…In a pathological study of 63 third trimester stillbirth cases, the most common form of brain injury was grey matter damage with neuronal necrosis not investigating migration capacities of progenitor cells [ 54 ]. Moreover, a study by Kono et al published interesting results for FGR from early-onset hypertension disorders of pregnancy (HDP) depending on their intrauterine growth status and gestational age at birth [ 55 ]. These results suggest that earlier onset of HDP with SGA (short for gestational age) may affect the death, cerebral palsy, and developmental delay at 3 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, increased production of IL-1β in the placenta stimulates the hypothalamic-pituitary-adrenal axis, and steroidogenesis occurs simultaneously in the fetus. 11,28 Hence, fetal steroids increase and promote the maturation of fetal organs.…”
Section: Discussionmentioning
confidence: 99%
“…Small for gestational age (SGA) is characterized by being below the 10th percentile of sex-specific birth weight based on the Japanese neonatal anthropometric chart for gestational age. 11…”
Section: Methodsmentioning
confidence: 99%